Factors Associated to Psychological Distress During the COVID-19 Pandemic Among Healthcare Workers in Ecuador - Ruiz-Frutos, Carlos; Arias-Ulloa, Cristian Arturo; Ortega-Moreno, Mónica; Romero-Martín, Macarena; Escobar-Segovia, Kenny F.; Adanaque-Bravo, Ingrid; Gómez-Salgado, Juan (International Journal of Public Health, 2022)
Objective: The global COVID-19 pandemic has challenged health systems. Healthcare professionals had to face harsh conditions that have caused psycho-emotional consequences. Ecuador has been one of the countries hit hardest by the pandemic in Latin America. The objective of this study was to analyse the levels of psychological distress among healthcare workers in Ecuador during the COVID-19 pandemic. Methods: A cross-sectional descriptive study was conducted with a convenience sample of 1056 healthcare professionals, assessing their psychological distress, physical symptoms of COVID-19, state of health, the preventive measures adopted, and the history of contact with people infected with the SARS-CoV2 virus. Results: It was obtained that 66.0% of the participants manifested psychological distress, with significantly higher levels in women with symptoms of COVID-19 and previous contact with infected people or objects (p<0.001). However, adherence to preventive measures and perception of health were associated with less psychological distress (p<0.001). Conclusions: The importance of monitoring the mental health of healthcare workers during the COVID-19 pandemic was confirmed, having identified factors associated with the development of psychological distress among professionals in Ecuador.